Tricuspid Valve Repair after Previous Mitral Valve Surgery - Pfannmueller, Bettina; Misfeld, Martin; Haensig, Martin; Davierwala, Piroze; Mohr, Friedrich Wilhelm (The Thoracic and Cardiovascular Surgeon, 2017)
Tricuspid valve (TV) regurgitation in patients after previous mitral valve surgery is usually a secondary failure and conditioned by a long-lasting left-sided valve failure. TV surgery in these patients represents a high-risk procedure regarding the operative strategy and perioperative management. This article will discuss the indication for TV surgery in patients with secondary TV regurgitation and previous mitral valve surgery, the choice of surgical access, as well as TV repair techniques and their postoperative results.
Keywords: secondary tricuspid valve regurgitation; reoperation; previous mitral valve surgery